完整家系中KIR单体型对父母亲缘供者单倍体造血干细胞移植预后的影响 (Zhonghua Xue Ye Xue Za Zhi, 2016)
OBJECTIVE: To investigate the role of different immunoglobulin-like receptor (KIR) haplotypes in haplo-identical hematopoietic stem cell transplantation (HSCT). METHODS: Killer cell KIR genotyping was performed on 468 individuals from 156 unrelated families by PCR-SSP. A total of 624 KIR haplotypes from the parents were used for haplotype analysis. Ninety-two patients received haplo-identical HSCT from one of the parents. RESULTS: The family study showed segregation of one A haplotype and at least 20 unique B haplotypes. The frequency of haplotype A was 72.92% (455/624). The most commonly observed haplotypes in group B were B1, B2, and B3, present at a frequency of 10.26%, 5.77%, and 4.48%, respectively. Compared to KIR gene matched donors (n=17), grafts from KIR gene mismatched donors (n=14) had a positive effect on survival after haplo-identical HSCT for AML/MDS patients (OS: 88.2% vs 42.9%, P=0.015; RFS: 88.2% vs 35.7%, P=0.007). No effect was observed for ALL/NHL patients (OS: 76.0% vs 75.0%, P=0.727; RFS: 68.0% vs 65.0%, P=0.866). A significantly lower survival rate was observed for transplants from AA (n=52) and AB1/AB2 donors (n=15), compared to other group Bx donors (n=25) (OS: 53.3% vs 96.0%, P=0.017; RFS: 53.3% vs 92.0%, P=0.019). Meanwhile, the risk of relapse was much higher in AA group (n=52) compared to Bx group (n=40) (25.0% vs 5.0%, P=0.009). A higher risk of TRM was observed in AB1/AB2 group (P=0.012). In addition, transplant from donors carried Cen-B was associated with an increased survival compared with Cen-A homozygous donors (OS: 94.7% vs 68.5%, P=0.036; RFS: 89.5% vs 64.4%, P=0.045). CONCLUSION: Overall, KIR genotyping and haplotype analyses should be useful for selection of the most optimal donors with favorable KIR gene grafts. KIR gene mismatch donors should be preferred for AML/MDS patients. Selecting donors carried Cen-B and avoiding the selection of donors of KIR genotype AA/AB1/AB2 was strongly advisable for haplo-identical HSCT.